2020
DOI: 10.1016/j.heliyon.2020.e04245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biological investigations of potentially bioactive heterocyclic compounds containing 4-hydroxy coumarin

Abstract: In this paper, we have reported the synthesis of a series of heterocyclic azo dyes containing 4-hydroxy coumarin by diazo-coupling reaction. The structural aspect of the newly synthesized compounds was accomplished by various physico-chemical techniques like UV-Visible, FT-IR, NMR, and mass spectrometry. The computational calculations and geometrical optimization of the newly synthesized azo dyes were investigated by using Gaussian software with the help of Density functional theory (DFT)/B3LYP method using 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…[71] 7-(2-Chloroquinolin-4-yloxy)-4-methyl-2H-chromen-2-ones, Scheme 45, were synthesized by Balaji et al [72] from substituted 1,3-dichloroquinoline and 7-hydroxy-4-methylcoumarin using conventional or under ultrasonic irradiation conditions. Kavetsou et al [73] described the synthesis of new 3-aryl-5substituted-coumarin derivatives in three steps starting from phenylacetic acid and dihydroxyacetophenone, Scheme 46. The corresponding acetoxycoumarin derivatives were reactedwith hydrazine monohydrate in methanol before alkylation with geranylbromide.…”
Section: Reactivity Of Coumarinmentioning
confidence: 99%
See 1 more Smart Citation
“…[71] 7-(2-Chloroquinolin-4-yloxy)-4-methyl-2H-chromen-2-ones, Scheme 45, were synthesized by Balaji et al [72] from substituted 1,3-dichloroquinoline and 7-hydroxy-4-methylcoumarin using conventional or under ultrasonic irradiation conditions. Kavetsou et al [73] described the synthesis of new 3-aryl-5substituted-coumarin derivatives in three steps starting from phenylacetic acid and dihydroxyacetophenone, Scheme 46. The corresponding acetoxycoumarin derivatives were reactedwith hydrazine monohydrate in methanol before alkylation with geranylbromide.…”
Section: Reactivity Of Coumarinmentioning
confidence: 99%
“…Kavetsou et al [73] . described the synthesis of new 3‐aryl‐5‐substituted‐coumarin derivatives in three steps starting from phenylacetic acid and dihydroxyacetophenone, Scheme 46.…”
Section: Coumarin Synthesismentioning
confidence: 99%
“…In previous studies the substitution of aryl or azo group in 4-Hydroxy coumarin moiety has been reported which indicates admirable antimicrobial activities. 9) Some thiazole, pyridine, triazole and phenyl thiazole derivatives of 4-hyroxy coumarin was synthesised by J. Sahoo et al and evaluate their in-vitro antibacterial activities against patogens. 10) A Sabt et al synthesized coumarin-6-sulfonamide derivatives and investigated their anti-proliferative nature and conclude that all synthesized compounds was able to diminish the growth of cancer cell by blocking topoisomerase-2 enzyme while doxorubin used as reference drug.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of heterocyclic molecules has today become inevitable given its importance in human life. The biological interest [1,2,3] of these molecules is very broad and diversified. Several families of heterocyclic molecules are used as antiviral [4,5], anti tuberculosis [6,7], anti cancer [8,9,10], anti tuberculosis [11,12], anti malaria [13], anti fungus [14].…”
Section: Introductionmentioning
confidence: 99%